Sediment core description of GeoB24374-1 (GC36) recovered during R/V Sonne expedition SO278 at Sartori MV in the Calabrian Arc, Mediterranean Sea - Mechthild Doll; Nele Behrendt; Agathe Eijsink; Gerhard Bohrmann (PANGAEA, 2024)
Sediment core GeoB24374-1 (GC36) was collected during R/V Sonne expedition SO278 using a gravity corer. The position is close to the Sartori Mud Volcano located in the Calabrian accretionary prism (Mediterranean Sea). To capture the sedimentary structure, the gravity core was longitudinally split directly after recovery on board of cruise SO278 and the archive halve was photographed using the smartCIS1600 line scan technique of the MARUM GeoB Core repository at a 500-dpi resolution. To investigate lithological changes in more detail, a macroscopic core description is prepared. The core description provides information regarding core length, exact position, water depth, number of core sections, core image, color, lithology, sedimentary structures and a descriptive text. Sediment color was determined qualitatively using Munsell soil color charts.